Dictionary’ Use among Second Year Students of English at the University of Constantine 1 - BENZITOUNI, Amina Ouafa (Journal of Human Sciences, 2019)
Despite the dynamic growth of research into dictionary use, we are still far from getting definitive answers to many important questions regarding dictionary use. We still do not know much about how dictionaries are perceived and used by students. We are also ignorant of the problems students encounter while using them. So, this paper seeks to gather information about dictionary use among second year students of English at the University of Constantine 1.  The results of the study revealed that the dictionary is an elementary tool for learners. The Participants use different types of dictionaries in particular monolingual electronic ones. However, they lack the skills to use their dictionaries effectively because most of them have not received any instruction on dictionary use. Teachers, therefore, have to equip students with the necessary reference skills, which in turn will have a positive influence on students ‘dictionary use.